2001
DOI: 10.1002/1521-4141(200103)31:3<687::aid-immu687>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and tolerance factor of the human placenta induces IL-10 production

Abstract: Regeneration and tolerance factor (RTF) was originally identified in the placenta of mice and the isolated protein shown to have suppressive effects. In these studies, the gene cloned from thymus tissue was mapped to human chromosome 12. The role of recombinant RTF on cytokines was examined. In addition, we examined the human placenta by immunohistochemistry for RTF expression. RTF was expressed at the peripheral layer of cytotrophoblast in 7–9‐week‐old placentas. Using the RTF gene sequence, a recombinant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…V-ATPase A2 was highly expressed in the pre-implantation embryos (Jaiswal et al 2012). Embryo V-ATPase A2 was involved in the regulation of maternal immune responses that is crucial for the pregnancy establishment (Jaiswal et al 2011;Lee et al 2001). In addition, V-ATPase A2 also regulates the cytokine and chemokine networks that coordinate macrophage recruitment to the feto-maternal interface for placental growth and development (Jaiswal et al 2011).…”
Section: Introductionsupporting
confidence: 53%
“…V-ATPase A2 was highly expressed in the pre-implantation embryos (Jaiswal et al 2012). Embryo V-ATPase A2 was involved in the regulation of maternal immune responses that is crucial for the pregnancy establishment (Jaiswal et al 2011;Lee et al 2001). In addition, V-ATPase A2 also regulates the cytokine and chemokine networks that coordinate macrophage recruitment to the feto-maternal interface for placental growth and development (Jaiswal et al 2011).…”
Section: Introductionsupporting
confidence: 53%
“…It was shown that a2V-ATPase could modulate IL-1␤ secretion from a human macrophage cell line [15]. Furthermore, it has been found that the N-terminus domain of the a2V-ATPase caused an increase in IL-10 production and a considerable reduction in IL-2 production from stimulated T cells [9]. In addition, the N-terminus domain of the a2V-ATPase is expressed in cycling and pregnant endometrium and IL-1␤ increases its mRNA expression [16].…”
Section: Introductionmentioning
confidence: 70%
“…Because of the first identification of a2NTD as a major protein in the maintenance of pregnancy, its early effects were targeted to Th2 cytokines, such as IL-10 [9]. The current research was conducted to investigate the role of a2NTD in cytokine secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations